Oxygen-doped carbon nitride catalyst as well as preparation method and application thereof
By preparing oxygen-doped carbon nitride catalysts, the environmental protection and catalyst recovery problems in the existing technology of synthesizing sulfoxides from sulfides are solved, and efficient selective oxidation of sulfides to sulfoxides under mild conditions is achieved, which is suitable for fields such as drug synthesis.
Patent Information
- Application Number
- CN202510813182.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-09-05
AI Technical Summary
The existing technology has problems in the process of synthesizing sulfoxides from sulfides, such as the use of toxic oxidants, difficulty in recovering catalysts, harsh reaction conditions and high energy consumption. It is particularly environmentally unfriendly and unfriendly in drug synthesis.
Oxygen-doped carbon nitride catalyst is prepared by hydrothermal reaction and calcination and is used for selective oxidation of sulfides in green solvents. The catalyst can be recycled and uses oxygen in the air as the oxygen source.
The highly selective oxidation of sulfides to sulfoxides under mild conditions is achieved. The catalyst is easily recyclable, the reaction process is environmentally friendly and efficient, and has a wide range of adaptability, especially exhibiting excellent catalytic performance in the synthesis of drug molecules.
Smart Images

Figure CN120586908A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to an oxygen-doped carbon nitride catalyst and a preparation method and application thereof. Background Art
[0002] Sulfoxides are one of the most important functional groups in organic chemistry. Given their presence in a large number of pharmaceutically active compounds, many researchers in industry and academia have focused their attention on developing novel methods suitable for industrial production. Traditionally, the preparation of sulfoxides primarily involves the oxidation of sulfides, and a variety of oxidation methods have been developed.
[0003] Currently, there are three main methods for synthesizing sulfoxides from sulfides: oxidation with oxidants, electrochemical catalysis, and photocatalysis. Despite significant progress in homogeneous systems for the synthesis of sulfoxides from sulfides, finding environmentally friendly solvents and excellent, recyclable catalysts for highly selective oxidation under mild reaction conditions remains a challenge.
[0004] When preparing sulfoxides by oxidant oxidation, various oxidants have been successfully utilized, including H2O2, m-CPBA, KMnO4, etc. Although the developed methods are simple and effective, these systems still have some defects, such as the need for metal catalysts or excessive additives, and even the use of toxic and explosive oxidants, and excessive sulfoxide oxidation caused by excessive strong oxidants is difficult to avoid.
[0005] In the reported electrochemical oxidation methods, in addition to the need for excess electrolyte, some reaction systems also require the addition of acid or additives, making the post-processing of the reaction unfriendly.
[0006] In homogeneous photocatalytic systems, catalysts cannot be recycled. When the reaction involves sacrificial agents, toxic and harmful waste may be produced. The sacrificial agents are generally toxic themselves, which is undesirable when synthesizing active drug molecules. Moreover, a large part of the photoreactions require the use of high-power lamps, which consumes a lot of energy. Summary of the Invention
[0007] The purpose of the present invention is to overcome the defects in the prior art and provide an oxygen-doped carbon nitride catalyst and a preparation method and application thereof.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing an oxygen-doped carbon nitride catalyst, comprising the following steps:
[0010] (1) mixing melamine, an aqueous hydrogen peroxide solution, and acetonitrile, and performing a hydrothermal reaction to obtain a precursor material;
[0011] (2) The precursor material is calcined to obtain the oxygen-doped carbon nitride catalyst.
[0012] Preferably, the mass fraction of the hydrogen peroxide aqueous solution in step (1) is 20 to 40 wt%.
[0013] Preferably, the mass volume ratio of melamine, aqueous hydrogen peroxide solution and acetonitrile in step (2) is 2-4 g: 10-20 mL: 10-20 mL.
[0014] Preferably, the temperature of the hydrothermal reaction in step (1) is 160-200°C.
[0015] Preferably, the hydrothermal reaction time in step (1) is 20 to 30 hours.
[0016] Preferably, the starting temperature of the calcination in step (2) is 20-40°C; and the heating rate is 1-3°C / min.
[0017] Preferably, the target temperature of the calcination in step (2) is 500-600° C., and the holding time after reaching the target temperature is 1-3 hours.
[0018] The present invention also provides an oxygen-doped carbon nitride catalyst prepared by the preparation method of the oxygen-doped carbon nitride catalyst.
[0019] The present invention also provides application of the oxygen-doped carbon nitride catalyst in the selective oxidation of sulfides to sulfoxides.
[0020] Preferably, the structure of the sulfide is as follows:
[0021]
[0022] Among them, R 1 is methyl, ethyl or phenyl; R 2 、R 3 、R 4 R is independently a hydrogen, methyl, methoxy, trifluoromethoxy, cyano, acyl, nitro or halogen atom; 5 is methyl or benzyl.
[0023] The present invention provides a method for preparing an oxygen-doped carbon nitride catalyst, comprising the following steps: (1) mixing melamine, an aqueous hydrogen peroxide solution and acetonitrile, and performing a hydrothermal reaction to obtain a precursor material; (2) calcining the precursor material to obtain the oxygen-doped carbon nitride catalyst. Compared with the prior art, the present invention has the following advantages: (1) the synthesis process of the catalyst is simple, and the raw materials for synthesizing the catalyst are cheap and easily available, and the equipment required for synthesizing the catalyst is simple and easy to operate. (2) The catalyst has excellent catalytic performance for the selective oxidation of sulfides, good substrate adaptability, and is easy to recycle and reuse. After multiple uses, the yield is still very high. (3) Currently, there are very few reports on the adaptability of photocatalytic heterogeneous oxidation to substrate expansion in drug molecules. The present invention provides an application method for a metal-free photocatalyst for the efficient selective oxidation of sulfides without additional additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the oxygen-doped carbon nitride catalyst prepared in Example 1;
[0025] Figure 2 These are XRD characterization patterns of the catalysts prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing an oxygen-doped carbon nitride catalyst, comprising the following steps:
[0027] (1) mixing melamine, an aqueous hydrogen peroxide solution, and acetonitrile, and performing a hydrothermal reaction to obtain a precursor material;
[0028] (2) The precursor material is calcined to obtain the oxygen-doped carbon nitride catalyst.
[0029] In the present invention, the mass fraction of the aqueous hydrogen peroxide solution in step (1) is preferably 20 to 40 wt%, more preferably 25 to 35 wt%, and even more preferably 28 to 32 wt%.
[0030] In the present invention, the mass volume ratio of melamine, aqueous hydrogen peroxide solution and acetonitrile in step (2) is preferably 2-4 g:10-20 mL:10-20 mL, more preferably 2.5-3.5 g:12-18 mL:12-18 mL, and more preferably 2.8-3.2 g:14-16 mL:14-16 mL.
[0031] In the present invention, the stirring time of the mixing in step (1) is preferably 2 to 4 hours, more preferably 2.5 to 3.5 hours, and even more preferably 2.8 to 3.2 hours.
[0032] In the present invention, the temperature of the hydrothermal reaction in step (1) is preferably 160-200°C, more preferably 165-195°C, and even more preferably 170-190°C.
[0033] In the present invention, the time of the hydrothermal reaction in step (1) is preferably 20 to 30 hours, more preferably 22 to 28 hours, and even more preferably 24 to 26 hours.
[0034] In the present invention, after the hydrothermal reaction in step (1) is completed, the reaction system is centrifuged and the solid obtained by centrifugation is washed, and the washing is carried out in sequence using acetonitrile, water, anhydrous ethanol, and anhydrous ether; the number of washing times for each reagent is preferably 2 to 3 times.
[0035] In the present invention, the washed solid is dried under vacuum conditions; the drying temperature is preferably 30-50°C, more preferably 35-45°C, and more preferably 38-42°C; and the solid is dried to a constant weight to obtain a precursor material.
[0036] In the present invention, the calcination in step (2) is carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen or argon.
[0037] In the present invention, the starting temperature of the calcination in step (2) is preferably 20-40°C, more preferably 25-35°C, and more preferably 28-32°C; the heating rate is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, and more preferably 1.8-2.2°C / min.
[0038] In the present invention, the target temperature of the calcination in step (2) is preferably 500-600°C, more preferably 520-580°C, and more preferably 540-560°C; the holding time after reaching the target temperature is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 1.8-2.2h.
[0039] In the present invention, after the calcination in step (2) is completed, the temperature is cooled, and the cooling rate of the cooling is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, and more preferably 1.8-2.2°C / min; the target temperature of the cooling is preferably 20-40°C, more preferably 25-35°C, and more preferably 28-32°C; and after the cooling is completed, the oxygen-doped carbon nitride catalyst is obtained.
[0040] The present invention also provides an oxygen-doped carbon nitride catalyst prepared by the preparation method of the oxygen-doped carbon nitride catalyst.
[0041] The present invention also provides application of the oxygen-doped carbon nitride catalyst in the selective oxidation of sulfides to sulfoxides.
[0042] In the present invention, the structure of the sulfide is as follows:
[0043]
[0044] Among them, R 1 is methyl, ethyl or phenyl; R 2 、R 3 、R 4 R is independently a hydrogen, methyl, methoxy, trifluoromethoxy, cyano, acyl, nitro or halogen atom; 5 is methyl or benzyl.
[0045] In the present invention, in the oxidation reaction of selectively oxidizing sulfide to sulfoxide, ethanol is used as a green solvent, and the oxygen-doped carbon nitride catalyst can be recycled; the reaction atmosphere of the oxidation reaction is air, and the oxygen in the air is used as the oxygen source, and no high-purity oxygen or other oxidants or auxiliary agents are required for the oxidation reaction.
[0046] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0047] Example 1
[0048] Accurately weigh 3.00 g of melamine, then measure 15 mL of aqueous hydrogen peroxide solution (30 wt%) and 15 mL of acetonitrile and mix and stir for 3 hours, then hydrothermally react at 180 ° C for 24 hours and naturally cool to room temperature. Take out the reaction solution and centrifuge it, wash it with acetonitrile, deionized water, anhydrous ethanol, and anhydrous ether 3 times each; the obtained solid is vacuum dried at 40 ° C to constant weight to obtain a white crystalline powder, which is the precursor material. The precursor material is placed in a nitrogen atmosphere, and the heating program is: initial temperature 30 ° C, heating to 550 ° C at a heating rate of 2 ° C / min, keeping warm for 2 hours, and then cooling to 30 ° C at the same rate of 2 ° C / min. After taking it out, grind it into powder with a mortar, and the resulting light yellow powder is the oxygen-doped carbon nitride catalyst, recorded as OCN.
[0049] Comparative Example 1
[0050] Accurately weigh 3.00g of melamine and grind it in a mortar. Then, transfer the powder to a porcelain boat and place it in a tube furnace, calcining it at high temperature under a nitrogen flow. The tube furnace temperature program is as follows: initially at 30°C, increase the temperature at a rate of 2°C / min to 550°C, maintain this temperature for 2 hours, and then cool it down to 30°C at the same rate of 2°C / min. The resulting yellow powder is the g-C3N4 catalyst.
[0051] The oxygen-doped carbon nitride catalyst prepared in Example 1 was observed under an electron microscope. The scanning electron microscope image is as follows: Figure 1 As shown, from Figure 1It can be seen that the catalyst has a tubular structure with a relatively flat surface and many small holes.
[0052] The catalysts prepared in Example 1 and Comparative Example 1 were characterized by XRD. Figure 2 As shown in the figure, compared with the standard card, the g-C3N4 material shows diffraction peaks at 2θ = 13.2° and 27.3°, representing the (100) and (002) crystal planes of the material, respectively, indicating that the material contains triazine ring structures and π-π stacking structures. The incorporation of oxygen does not affect the crystal structure of the carbon nitride material. The peak position is almost the same as that of the g-C3N4 material, and the peak height at 27.3° is slightly lower than that of the g-C3N4 material.
[0053] The catalyst materials prepared in Example 1 and Comparative Example 1 were used in the oxidation reaction of phenethyl sulfide, and the reaction equation was as follows:
[0054]
[0055] The specific process involved adding 0.2 mmol of phenylethyl sulfide, 20 mg of the catalyst material, and 3 mL of ethanol as the solvent to a 38 mL sealed tube under air. Irradiation with 10W 465 nm LED blue light was performed, and the reaction was stirred at room temperature for 15 hours. The reaction mixture was centrifuged, the supernatant was concentrated, and then purified by column chromatography.
[0056] Using the oxygen-doped carbon nitride catalyst prepared in Example 1, the separation yield of the oxidation product was 98%; using the g-C3N4 catalyst prepared in Comparative Example 1, the separation yield of the oxidation product was 70%.
[0057] Comparative Example 2
[0058] Accurately weigh 20.00 g of cyanoguanidine and 1.82 g of boric acid into 50 mL of distilled water, then stir the mixed suspension at 90°C. After evaporation of the water, the dried powder is placed in a ceramic crucible and heat-treated in a muffle furnace. Heat in air at a rate of 2°C / min to 550°C and hold for 2 hours. Then, cool to room temperature at the same rate of 2°C / min. Collect the yellow material and grind it into a powder in an agate mortar to obtain the boron-doped carbon nitride (BCN) catalyst.
[0059] The same oxidation reaction process of thiophene was adopted as in Example 1, and the isolated yield of the oxidation product was 38%.
[0060] Comparative Example 3
[0061] 3.0 g of dicyandiamide was dissolved in 15 mL of deionized water with stirring, followed by the addition of 0.2 g of diammonium hydrogen phosphate. The solution was heated to 90°C, and the solvent evaporated to obtain a solid product. The solid product was dried at 100°C and then heated to 550°C under a nitrogen atmosphere at a heating rate of 2°C / min and held for 2 hours. The temperature was then cooled to room temperature at the same rate of 2°C / min to obtain a yellow product, the phosphorus-doped carbon nitride (PCN) catalyst.
[0062] The same oxidation reaction process of thiophene was adopted as in Example 1, and the isolated yield of the oxidation product was 75%.
[0063] Comparative Example 4
[0064] Accurately weigh 5g of urea, 0.5g of melamine, and 1g of thiourea into 50mL of distilled water, then stir the mixed suspension at 90°C. After evaporation of the water, the dried powder is placed in a ceramic crucible and heat-treated in a muffle furnace. The mixture is heated in air at a rate of 2°C / min to 550°C and held for 2 hours. The temperature is then cooled to room temperature at the same rate of 2°C / min. The yellow material is collected and ground into a powder in an agate mortar to yield the sulfur-doped carbon nitride (SCN) catalyst.
[0065] The same oxidation reaction process of thiophene was adopted as in Example 1, and the isolated yield of the oxidation product was 58%.
[0066] Comparative Example 5
[0067] Accurately weigh 5g of urea, 0.5g of melamine, and 0.5g of copper nitrate hydrate into 50mL of distilled water, then stir the mixed suspension at 90°C. After evaporation of the water, the dried powder is placed in a ceramic crucible and heat-treated in a muffle furnace. The mixture is heated in air at a rate of 2°C / min to 550°C and held for 2 hours. The temperature is then lowered to room temperature at the same rate of 2°C / min. The brownish-yellow material is collected and ground into a powder in an agate mortar to yield the copper-doped carbon nitride (CuCN) catalyst.
[0068] The same oxidation reaction process of thiophene was adopted as in Example 1, and the isolated yield of the oxidation product was 30%.
[0069] Comparative Example 6
[0070] Accurately weigh 5g of urea, 0.5g of melamine, and 1g of potassium chloride into 50mL of distilled water, then stir the mixed suspension at 90°C. After evaporation of the water, the dried powder is placed in a ceramic crucible and heat-treated in a muffle furnace. The mixture is heated in air at a rate of 2°C / min to 550°C and held there for 2 hours. The temperature is then lowered to room temperature at the same rate of 2°C / min. The brownish-yellow material is collected and ground into a powder in an agate mortar to yield the potassium-doped carbon nitride (KCN) catalyst.
[0071] The same oxidation reaction process of thiophene as in Example 1 was adopted, and the isolated yield of the oxidation product was 68%.
[0072] Comparative Example 7
[0073] 5 mL of tetrabutyl titanate and 0.6 mL of hydrofluoric acid were added to a 25 mL high-pressure hydrothermal reactor. The reaction was carried out at 200°C for 24 hours, and then naturally cooled to room temperature. Subsequently, the resulting white solid was centrifuged, washed with deionized water and anhydrous ethanol multiple times, and vacuum dried. The resulting white powder was the nano-TiO2 material catalyst.
[0074] The same oxidation reaction process of thiophene was adopted as in Example 1, and the isolated yield of the oxidation product was 78%.
[0075] Comparative Example 8
[0076] The same oxidation reaction process of phenethyl sulfide as in Example 1 was adopted, except that different light sources were used for irradiation. The isolated yields of the oxidation products are shown in Table 1.
[0077] Table 1 Yields under different light sources
[0078]
[0079]
[0080] NR means no reaction, the same below.
[0081] Comparative Example 9
[0082] The same oxidation reaction process of thiophene was adopted as in Example 1, except that it was carried out in different solvents. The isolated yield of the oxidation product is shown in Table 2.
[0083] Table 2 Yields in different solvents
[0084]
[0085] Comparative Example 10
[0086] The same oxidation reaction process of thiophene as in Example 1 was adopted, except that the reaction time was different. The isolated yield of the oxidation product is shown in Table 3.
[0087] Table 3 Yields at different reaction times
[0088]
[0089] Comparative Example 11
[0090] The oxidation reaction process of phenethyl sulfide was the same as that of Example 1, except that the reaction atmosphere was different. The isolated yield of the oxidation product is shown in Table 4.
[0091] Table 4 Yields under different reaction atmospheres
[0092] Reaction atmosphere Nitrogen oxygen Product yield (%) NR 98
[0093] Experimental Example 1
[0094] The same oxidation reaction process as in Example 1 was used, but the sulfide substrate was changed. The isolated yields of the corresponding oxidation products are shown in Table 5.
[0095] Table 5 Yields of different sulfide substrates
[0096]
[0097]
[0098]
[0099]
[0100] As can be seen from the above examples, the oxygen-doped carbon nitride catalyst provided by the present invention has a separation yield of oxidation products of 98%, which is much higher than that of catalysts doped with other elements, and has excellent reaction catalytic performance.
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing an oxygen-doped carbon nitride catalyst, characterized in that: It includes the following steps: (1) mixing melamine, an aqueous hydrogen peroxide solution, and acetonitrile, and performing a hydrothermal reaction to obtain a precursor material; (2) The precursor material is calcined to obtain the oxygen-doped carbon nitride catalyst.
2. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 1, wherein: The mass fraction of the hydrogen peroxide aqueous solution in step (1) is 20 to 40 wt%.
3. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 2, wherein: The mass volume ratio of melamine, hydrogen peroxide solution and acetonitrile in step (2) is 2-4 g: 10-20 mL: 10-20 mL.
4. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 3, wherein: The temperature of the hydrothermal reaction in step (1) is 160-200°C.
5. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 4, wherein: The hydrothermal reaction time in step (1) is 20 to 30 hours.
6. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 5, wherein: The starting temperature of the calcination in step (2) is 20-40° C.; the heating rate is 1-3° C. / min.
7. The method for preparing the oxygen-doped carbon nitride catalyst according to claim 6, wherein: The target temperature of the calcination in step (2) is 500-600° C., and the holding time after reaching the target temperature is 1-3 hours.
8. The oxygen-doped carbon nitride catalyst prepared by the method for preparing the oxygen-doped carbon nitride catalyst according to any one of claims 1 to 7.
9. Use of the oxygen-doped carbon nitride catalyst according to claim 8 in the selective oxidation of sulfides to sulfoxides.
10. Use of the oxygen-doped carbon nitride catalyst in the selective oxidation of sulfide to sulfoxide according to claim 9, characterized in that: The structure of the sulfide is shown below: Among them, R 1 is methyl, ethyl or phenyl; R 2 、R 3 、R 4 R is independently a hydrogen, methyl, methoxy, trifluoromethoxy, cyano, acyl, nitro or halogen atom; 5 is methyl or benzyl.
Citation Information
Cited By
2-aminopyrimidine modified carbon nitride material capable of efficiently generating singlet oxygen as well as preparation method and application of 2-aminopyrimidine modified carbon nitride material
CN121695912A